Chapter 9. continuous flow synthesis of nanomaterials - Kulkarni, Amol A.; Jundale, Rajashri B. (Flow Chemistry, 2020)
Continuous flow synthesis of nanoparticles is now a well-accepted and reliable synthesis approach that gives consistent product properties. This chapter aims to do a critical analysis of the recent work in some of the relevant areas and gives specific recommendations where flow synthesis of nanomaterials can be realized as a reliable manufacturing process. The chapter also highlights the typical engineering issues that one needs to consider while transforming a batch synthesis protocol into continuous mode and its scale-up.

Understanding the role of solvent properties on reaction kinetics for synthesis of silica nanoparticles - Bari, Atul H.; Jundale, Rajashri B.; Kulkarni, Amol. A. (Chemical Engineering Journal, 2020)
The effect of various alcoholic solvents and their compositions on the size of silica particles synthesized through hydrolysis and condensation of tetraethyl orthosilicate (TEOS) is studied. The alcohols used are: Methanol, ethanol, propanol, i-propanol, butanol, pentanol, hexanol, octanol, decanol and do-decanol. Ethanol was used as a co-solvent with the higher molecular weight alcohols. Silica particles of size between 100 nm and 2 mu m were obtained by changing solvent composition. Concentrations of total soluble silica and silicic acid were measured and used for exploring the kinetics of hydrolysis and condensation reactions. Polarity, steric hindrance and viscosity of solvent were found to have a strong influence on the rate constants and size of silica nanoparticles. An attempt is made to correlate both final particle size and rate constants with dielectric constant, Wiener index and viscosity of the solvent.
Keywords: condensation; Hydrolysis; kinetics; silica particles; Solvents; Stober process

Insights into the synthesis and kinetics of silver-on-silica core-shell particles - Jundale, Rajashri B.; Bari, Atul H.; Kulkarni, Amol A. (Langmuir, 2023)
In this study, a heterogeneous nucleation and growthmodel hasbeen developed to explore the formation mechanism of silver-depositedsilica core-shell particles based on the reaction kinetics.To validate the core-shell model, the time-dependent experimentaldata were quantitatively examined and in situ reduction,nucleation, and growth rates were estimated by optimizing the concentrationprofiles of reactants and deposited silver particles. Using this model,we also attempted to predict the change in the surface area and diameterof core-shell particles. The concentration of the reducingagent, metal precursor, and reaction temperature were found to havea strong influence on the rate constants and morphology of core-shellparticles. Higher rates of nucleation and growth often produced thick,asymmetric patches that covered the entire surface, whereas lowerrates produced sparsely deposited silver particles with a sphericalshape. The result revealed that by simply tuning the process parametersand controlling the relative rates, the morphology of deposited silverparticles and the surface coverage can be controlled while retainingthe spherical shape of the core. The present study aims to offer comprehensivedata pertaining to the nucleation, growth, and coalescence processesof core-shell nanostructures which will aid in the developmentand understanding of the principles that govern the formation of nanoparticle-coatedmaterials.

Continuous flow synthesis of mesoporous silica particles with tunable size and structure - Jundale, Rajashri B.; Prasad, Bhagavatula L. V.; Devi, R. Nandini; Kulkarni, Amol A. (Industrial and Engineering Chemistry Research, 2024)
We have developed a continuous process to prepare mesoporous silica particles of different sizes and narrow size distribution in a tubular reactor. The method is based on the use of well-known Stober synthesis in the presence of cationic surfactant in methanol-water solvent system and trimethylbenzene as pore swelling agent to form porous silica particles. We observed that reaction parameters had enormous effects on particle size, distribution, and numerous morphological aspects. We demonstrated that these properties may be modified by adjusting the reaction temperature, base concentration, and surfactant concentration. MSPs of spherical morphology with variable size from 400 to 1000 nm produced with the surface area >600 m(2)/g and pore diameter of 2-4 nm. Large scale production is demonstrated by increasing reactor volume using 1/4 in. PTFE tubing from 20 to 163 mL, with this production of MSPs increased from 0.35 to 3 g/h. The method has been extended for high yield production at the kilogram scale using this approach, which will pave the way toward the industrialization of mesoporous silica based materials.

Scaling-up continuous production of mesoporous silica particles at kg scale: design & operational strategies - Jundale, Rajashri B.; Sonawane, Jayesh R.; Palghadmal, Anil V.; Jaiswal, Hemant Kumar; Deore, Hital S.; Kulkarni, Amol A. (Reaction Chemistry & Engineering, 2024)
This paper demonstrates a continuous flow pilot-scale production of highly porous mesoporous silica particles (MSPs) via a soft template based technique. The study presents pilot scale reactor design, fabrication and production of mesoporous silica particles with a 1 kg per day production rate. The extent of mixing and overall performance of the system were evaluated by conducting a hydrodynamic study, including the estimation of the heat transfer coefficient and dispersion number. Nanoparticle synthesis in a clogging-free manner is the key challenge in moving towards large scale production and commercial applications. This article presents a comprehensive study on the effect of key parameters for successful scaling up of the process. We have also addressed challenges faced and how these are overcome by troubleshooting the process. Different strategies were used to prevent the clogging of the reactor, which involved reactant dilution, periodic pulsation and slug flow (two phase flow). Among them, slug flow allows us to operate the reactor continuously for several hours without clogging and wall-deposition problems. It helped produce morphologically well-defined and near-monodisperse particles. With this process, the production is validated at a scale of 85 times compared to that of a laboratory system (from 22 mL to >1.5 L), enabling a production rate of 20-50 g h(-1).